PENGARUH FINANCIAL LITERACY DAN BEHAVIORAL FINANCE FACTORS TERHADAP KEPUTUSAN INVESTASI (STUDI TERHADAP INVESTOR SAHAM SYARIAH PADA GALERI INVESTASI SYARIAH UIN SUNAN AMPEL SURABAYA) - KHAIRUNIZAM; ISBANAH, YUYUN (Jurnal Ilmu Manajemen (JIM), 2019)
The development of the number of investors in Indonesia has increased from 2012 to 2018, especially for sharia investors. Investment decision making is based on rational and irrational attitudes of every investor. So that this study aims to determine the influence of financial literacy and behavioral finance factors (overconfidence, risk perception, loss aversion, and herding) on study investment decisions on sharia stock investors in the sharia investment gallery of UIN Sunan Ampel Surabaya. The analysis technique used in this study is multiple linear regression analysis with a total sample of 126 respondents. The results of this study show variable overconfidence and herding influence on investment decisions. Respondents have a high level of confidence in making investment decisions. In addition, respondents in making investment decisions are also based on other investors. Financial literacy in the respondents of this study is in the medium category, but this does not affect investment decision making because respondents feel they do not need to use knowledge in making investment decisions. Although the level of risk perception of respondents in the medium category and the level of loss aversion in the high category, respondents still tended to be brave and less careful in investing. Keywords: financial literacy; herding; investment decisions; loss aversion; overconfidence; risk perception